2019
DOI: 10.26434/chemrxiv.8862239
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic Screening of DMOF-1 with NH2, NO2, Br and Azobenzene Functionalities for Elucidation of Carbon Dioxide and Nitrogen Separation Properties

Abstract: In this study, dabco MOF-1 (DMOF-1) with four different functional groups (NH<sub>2</sub>, NO<sub>2</sub>, Br and azobenzene) has been successfully synthesized through systematic control of the synthesis condition of their parent framework. The functionalised DMOF-1 is characterized using various analytical techniques including PXRD, TGA and N<sub>2</sub> sorption. The effect of the various functional groups on the performance of the MOFs for post-combustion CO<sub>2&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Their findings demonstrated that a high density of azobenzene moieties per MOF unit cell changed the host-guest chemistry, providing the basis for the drastic switchable adsorption results [76]. More recently, an azobenzene functionalized gated MOF was studied for gas sorption by Ladewig and coworkers in 2019 [91].…”
Section: Lisa Type 2: Azobenzenes As Pendant Groupsmentioning
confidence: 99%
“…Their findings demonstrated that a high density of azobenzene moieties per MOF unit cell changed the host-guest chemistry, providing the basis for the drastic switchable adsorption results [76]. More recently, an azobenzene functionalized gated MOF was studied for gas sorption by Ladewig and coworkers in 2019 [91].…”
Section: Lisa Type 2: Azobenzenes As Pendant Groupsmentioning
confidence: 99%